Morphological characteristics and molecular identification of a wild Thai isolate of the tropical mushroom Hed Taen Rad (Macrocybe crassa) - TANAPAK INYOD; SURIYA SASSANARAKIT; ACHARA PAYAPANON; SUTTIPUN KEAWSOMPONG (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Inyod I, SassanarakitS, PayapanonA, Keawsompong S. 2017. Morphological characteristics and molecular identification of a wild Thai isolate of the tropical mushroom Hed Taen Rad (Macrocybe crassa). Biodiversitas 18: 221-228. Hed Taen Rad or Macrocybe crassa is a wild edible mushroom found in Thailand. It has a large fruiting body with a meaty texture and a delicious taste. Five strains of Hed Taen Rad; DOA, DOA-1, DOA-4, DOA-7 and DOA-10 were tested in different media, pH values and temperatures to measure mycelium growth kinetics and identify mycelia and basidiomata. Results indicated that mushroom mycelial growth rates were highest on MEA medium at pH values between 8 and 10, and temperatures between 20Â°C and 30Â°C. Identification of the isolates was based on the morphology characteristics of the basidiomata were closely similar to M. crassa (Berk.), and different from M. gigantea (Massee). For molecular analysis by sequencing of their internal transcribed spacer (ITS) regions was identified as a T. giganteum since limited ITS rDNA sequences from M. crassa exist in public databases. Therefore, the identification of five strains of Hed Taen Rad using molecular methods could be erroneous. Therefore, morphology characteristics study is suitable for further analysis method on genetic study of Hed Taen Rad. Keywords: Hed Taen Rad, Macrocybe crassa, molecular analysis, morphological characteristics